EDUCAÇÃO FÍSICA NO ENSINO TÉCNICO - Müller, Deise Margô (Revista Liberato, 2013)
This article synthesizes a research accomplisched with the purpose of identifying the collaboration of Physical Education at the education of technical teaching students. The research is based on the qualitative methodology because this is one of the ways that has been utilized to interpret social realities.It also presents legal aspects of Physical Education teaching and the vision of many authors about the education of the professionals who work at this area. At the end of this research was possible describe and interpret the context of the school analysed and suggest directions for keeping on this research.